(untitled) (Hoboken, N.J., 2008)
Bringing together an international group of experts from across all health-related disciplines, Comprehensive Handbook of Clinical Health Psychology bridges the gap between health psychology and medicine to provide you with the up-to-date and relevant information and strategies you need to address both the physical and mental health care needs of your clients. Written in an accessible, reader-friendly manner, this reference covers the conditions and trends that have become most prevalent in the field of health psychology today
Keywords: Clinical health psychology,Behavioral Medicine,Tâm lý học sức khỏe lâm sàng,Y học hành vi; Handbooks, manuals, etc.,methods,phương pháp